Developing women entrepreneurs through guided and funded business start-ups in South Africa - Jali, Someleze; Tengeh, Robertson; Makoza, Frank (Journal of Economic Development, Environment and People, 2023)
South African women own a modest share of businesses while being the majority of the population. Increasing the number of female entrepreneurs in South Africa is expected to reduce poverty and unemployment, empower women, ensure equity, and strengthen the economy. This article examined the development of women entrepreneurs in Cape Town through guided and funded business start-ups. Data were collected using a qualitative technique based on purposive sampling through semi-structured interviews with 17 participants. An interpretive paradigm and an explorative design were employed. The data was analysed using the ATLAS.ti software. According to the participants, many women-owned business start-ups are neither funded nor guided. The findings revealed that many women entrepreneurs do not support one another in business start-ups in Cape Town. Moreover, minimal effort is put into interventions by both government and the private sector to abate gender discrimination and eliminate the exclusion of women entrepreneurs. There are instances of gender bias that impede the development of women entrepreneurs. The findings confirm that the development of women entrepreneur-focused funding for start-ups has received scant attention in Cape Town. Many women entrepreneurs still do not receive developmental support. Among the proposed interventions to improve women entrepreneurship, start-up funding and guidance are platforms that encourage informal businesses to become formal and penetrate formal financial networks. This paper argues for lending models best suited for women entrepreneurs in South Africa.